Transcriptional activation of a conserved sequence element by ras requires a nuclear factor distinct from c-fos or c-jun. - Owen, R D (1990)
The expression of transforming growth factor beta type 1 mRNA was increased by conditional expression of ras. A 31-base-pair sequence found approximately 420 base pairs upstream of the gene encoding human transforming growth factor beta 1 acted as a ras-responsive enhancer element in transient transfection assays. The human sequence contains the element TGACTCT that also is found in a murine ras-responsive enhancer. Analysis of nuclear factors present in cells stably transformed by ras indicated that both human and murine sequences were recognized by the same nuclear factor. The role of fos and jun in ras transcriptional activation was analyzed in transfection assays using murine elements that contained either TGACTCT or TGAGTAA. These experiments showed that while both elements are activated by fos/jun expression to nearly the same event, only the former element responded to ras. In addition, activation of reporters containing TGACTCT is 6-fold higher by ras than by fos/jun. Gel retention experiments revealed that the nuclear factor present in cells transformed by ras exhibited the same sequence preference as demonstrated in the transient transfection assays. UV-crosslinking experiments identify a protein of apparent molecular mass 120 kDa that recognizes the ras-responsive element. This work identifies a persistent signal transduction pathway that links ras to nuclear transcription and indicates that a 120-kDa protein is a target of this pathway.